2017
DOI: 10.1177/1758834017698643
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-induced muscle wasting: latest findings in prevention and treatment

Abstract: Cancer cachexia is a severe and disabling clinical condition that frequently accompanies the development of many types of cancer. Muscle wasting is the hallmark of cancer cachexia and is associated with serious clinical consequences such as physical impairment, poor quality of life, reduced tolerance to treatments and shorter survival. Cancer cachexia may evolve through different stages of clinical relevance, namely pre-cachexia, cachexia and refractory cachexia. Given its detrimental clinical consequences, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
137
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 146 publications
(186 reference statements)
1
137
1
8
Order By: Relevance
“…Given the complex pathologic process of cachexia and sarcopenia and according to increasing evidence, these interventions should ideally be multimodal and at least consist of nutritional support, physical exercise perhaps combined with pharmacological interventions. This could prevent (pre) cachectic patients from developing refractory cachexia, a stage of cancer cachexia associated with progressive cancer not responding to anticancer treatment, low performance status, and short life expectancy . In our study, we observed a median decrease of 4% in SMI and an increase of sarcopenic (obese) patients after only three cycles of chemotherapy, stressing the urgency that these preventive measures need to be applied in an early stage of treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Given the complex pathologic process of cachexia and sarcopenia and according to increasing evidence, these interventions should ideally be multimodal and at least consist of nutritional support, physical exercise perhaps combined with pharmacological interventions. This could prevent (pre) cachectic patients from developing refractory cachexia, a stage of cancer cachexia associated with progressive cancer not responding to anticancer treatment, low performance status, and short life expectancy . In our study, we observed a median decrease of 4% in SMI and an increase of sarcopenic (obese) patients after only three cycles of chemotherapy, stressing the urgency that these preventive measures need to be applied in an early stage of treatment.…”
Section: Discussionmentioning
confidence: 59%
“…The strong correlations that we have identified between a high relative frequency of EM CD8 + T cells and stronger HGS and chest press capacity in patients with cancer suggest that CD8 + T cell surveillance might continue during cancer recurrence in some patients. Some control of tumour burden might then reduce the detrimental effect that tumour growth has on muscle function resulting in stronger muscle measures . Our data do not address whether the CD8 + EM cells in cancer participants with greater muscle strength contain cancer‐specific cells.…”
Section: Discussionmentioning
confidence: 75%
“…In people with cancer, reduced muscle mass and strength are also negatively associated with disease‐free survival and overall survival . Tumour growth is known to promote loss of muscle mass and function; however, the specific mechanisms mediating this effect are incompletely understood . Cancer‐specific T cell responses that target cancer cells might indirectly protect muscle mass and function by reducing tumour burden .…”
Section: Introductionmentioning
confidence: 99%
“…Based on results from murine models, recent clinical trials have aimed to unravel the efficiency of blocking activin signalling in patients with cachexia or muscle dystrophy. Clinical trials involving ACVR2B decoy receptors, however, were terminated due to severe adverse effects, including bleeding . More specific antibodies directed towards the ACVR2B are being tested in clinical trials; however, because ACVR2 are central receptors for multiple TGFβ family members, and our study points to the central role of activin A, specific inhibition of activin A itself may prove less invasive and equally efficient.…”
Section: Discussionmentioning
confidence: 93%